Ibn-e-rushd - Irshad ul Haq", Qudusi (Feroz Sons Pakistan, 2005)
"Ibn-e-Rushd, also known as Averroes, was a medieval Andalusian philosopher, jurist, and polymath renowned for his commentaries on Aristotle and contributions to Islamic philosophy."